Local woman missing - Kubica, Mary (Park Row Books, 2021)
"Shelby Tebow is the first to go missing. Not long after, Meredith Dickey and her six-year-old daughter, Delilah, vanish just blocks away from where Shelby was last seen, striking fear into their once-peaceful community. Are these incidents connected? After an elusive search that yields more questions than answers, the case eventually goes cold. Now, eleven years later, Delilah shockingly returns. Everyone wants to know what happened to her, but no one is prepared for what they'll find"--